World Beats - Fazzino, Jimmy, 1981-; Project Muse. (Hanover, New Hampshire : Dartmouth College Press, 2016)
"This ... book explores Beat Generation writing from a transnational perspective, using the concept of worlding to place Beat literature in conversation with a far-reaching network of cultural and political formations. Countering the charge that the Beats abroad were at best naïve tourists seeking exoticism for exoticism's sake, World Beats finds that these writers propelled a highly politicized agenda that sought to use the tools of the earlier avant-garde to undermine Cold War and postcolonial ideologies and offer a new vision of engaged literature. With fresh interpretations of central Beat authors Jack Kerouac, Allen Ginsberg, and William Burroughs - as well as usually marginalized writers like Philip Lamantia, Ted Joans, and Brion Gysin - World Beats moves beyond national, continental, or hemispheric frames to show that embedded within Beat writing is an essential universality that brought America to the world and the world to American literature"--From publisher's description.
A world, a sweet attention : Jack Kerouac's subterranean itineraries -- The Beat manifesto : avant-garde poetics, Black Power, and the worlded circuits of African American Beat writing -- A multilayered inspiration : Philip Lamantia, Beat poet -- Cut-ups and composite cities : the Latin American origins of Naked Lunch -- For Africa ... for the world : Brion Gysin and the postcolonial Beat novel -- Columbus Avenue revisited : Maxine Hong Kingston and the post-Beat canon.
English.
Description based on print version record.
Keywords: Literature and transnationalism; Beats (Persons); American literature; Beat literature; LITERARY CRITICISM / American / General; LITERARY CRITICISM -- General; Beat generation; Litterature americaine -- 20e siecle -- Histoire et critique; Beatniks; Litterature et transnationalisme; Literature and transnationalism; American literature -- 20th century -- History and criticism; Beats (Persons); Beat literature -- Political aspects; Beat literature -- History and criticism; Critiques litteraires; Literary criticism; Criticism, interpretation, etc; Literary criticism; Electronic books